2012
DOI: 10.1007/s11307-012-0563-1
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Turbo-Spin-Echo Amide Proton Transfer MR Imaging at 3-Tesla and Its Application to High-Grade Human Brain Tumors

Abstract: Purpose Amide proton transfer (APT) imaging is able to extend the achievable MRI contrast to the protein level. In this study, we demonstrate the feasibility of applying a turbo spin echo (TSE)-based, three-dimensional (3D) APT sequence into routine clinical practice for patients with brain tumors. Procedures Experiments were performed on a Philips 3T MRI scanner using an eight-channel phased-array coil for reception. A fast 3D APT sequence with a TSE acquisition was proposed (saturation power, 2 μT; saturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 29 publications
2
66
0
Order By: Relevance
“…An off-resonance continuous-wave radiofrequency saturation pulse was used. APT single-section imaging was performed, and the saturation time, at 2 T excitation power, was 500 ms (the maximum time available for this body coil [22][23][24] ). The acquisition mode was TSE, and the factor was 38.…”
Section: Apt Data Acquisition and Processingmentioning
confidence: 99%
“…An off-resonance continuous-wave radiofrequency saturation pulse was used. APT single-section imaging was performed, and the saturation time, at 2 T excitation power, was 500 ms (the maximum time available for this body coil [22][23][24] ). The acquisition mode was TSE, and the factor was 38.…”
Section: Apt Data Acquisition and Processingmentioning
confidence: 99%
“…For these protein ST effects, several interesting correlations have been shown that might play a role in vivo and especially in pathologies: dependence on intracellular pH (5,(10)(11)(12)(13), protein concentration (8,13), or protein folding (14,15) and aggregation states (16). Already, the use for brain tumor detection (6,(17)(18)(19)(20), grading (21), and possible differentiation of tumor recurrence and radiation necrosis (22) has been shown to be feasible by proteinbased saturation transfer MRI.…”
Section: Introductionmentioning
confidence: 99%
“…Amide proton transfer (APT) imaging [4, 5] is an important molecular MRI technique that is sensitive to endogenous mobile proteins and peptides in tissue [6]. Prior data suggest that there are consistent APT-weighted hyperintensities in animal glioma models [7, 8] and in high-grade gliomas in patients [9-11]. These studies show that APT imaging for malignant brain tumors has much potential, for example, to differentiate between tumor and peritumoral edema, to separate high-grade from low-grade gliomas, and to detect high-grade gliomas that do not show gadolinium enhancement, all without exposure to contrast agents.…”
Section: Introductionmentioning
confidence: 99%